Damping of Subsynchronous Resonance in a Hybrid System With a Steam-Turbine Generator and an Offshore Wind Farm Using a Unified Power-Flow Controller; IEEE Transactions on Industry Applications; Vol. 57, iss. 1 - Li Wang; Shi-Ying Zeng; Wen-Kai Feng; Prokhorov A. V. Anton Viktorovich; Mokhlis H. Hazlie; Chua Kein Huat; Tripathy M. Manoj (2021, 2021)
Title screen